The EEC preferences: A critical evaluation - Richard N. Cooper (Intereconomics, 1972)
On July 1, 1971, the European Community Introduced a system of generalized tariff preferences for less developed countries. This followed nearly five years of intensive discussion among the major industrial countries about how best to respond to an appeal by the UNCTAD to help improve the trading opportunities of LDCs.
Keywords: 330; Foreign Trade